Synthesis and preliminary preclinical evaluation of fluorine-18 labelled isatin-4-(4-methoxyphenyl)-3-thiosemicarbazone ([18F]4FIMPTC) as a novel PET tracer of P-glycoprotein expression - Joost Verbeek; Jonas Eriksson; Stina Syvänen; Marc Huisman; Robert C. Schuit; Carla F. M. Molthoff; Rob A. Voskuyl; Elizabeth C. de Lange; Adriaan A. Lammertsma; Albert D. Windhorst (SpringerOpen, 2018)
Abstract Background Several P-glycoprotein (P-gp) substrate tracers are available to assess P-gp function in vivo, but attempts to develop a tracer for measuring expression levels of P-gp have not been successful. Recently, (Z)-2-(5-fluoro-2-oxoindolin-3-ylidene)-N-(4-methoxyphenyl)hydrazine-carbothioamide was described as a potential selective P-gp inhibitor that is not transported by P-gp. Therefore, the purpose of this study was to radiolabel two of its analogues and to assess their potential for imaging P-gp expression using PET. Results [18F]2-(4-fluoro-2-oxoindolin-3-ylidene)-N-(4-methoxyphenyl)hydrazine-carbothioamide ([18F]5) and [18F]2-(6-fluoro-2-oxoindolin-3-ylidene)-N-(4-methoxyphenyl)hydrazine-carbothioamide ([18F]6) were synthesized and both their biodistribution and metabolism were evaluated in rats. In addition, PET scans were acquired in rats before and after tariquidar (P-gp inhibitor) administration as well as in P-gp knockout (KO) mice. Both [18F]5 and [18F]6 were synthesized in 2-3% overall yield, and showed high brain uptake in ex vivo biodistribution studies. [18F]6 appeared to be metabolically unstable in vivo, while [18F]5 showed moderate stability with limited uptake of radiolabelled metabolites in the brain. PET studies showed that transport of [18F]5 across the blood-brain barrier was not altered by pre-treatment with the P-gp inhibitor tariquidar, and uptake was significantly lower in P-gp KO than in wild-type animals and indeed transported across the BBB or bound to P-gp in endothelial cells. Conclusion In conclusion, [18F]5 and [18F]6 were successfully and reproducibly synthesized, albeit with low radiochemical yields. [18F]5 appears to be a radiotracer that binds to P-gp, as showed in P-gp knock-out animals, but is not a substrate for P-gp.